Unusual hail storms during May 2002 in Chennai and its suburbs – A study using data from a single Doppler Weather Radar (MAUSAM, 2004)
Climatologically, hail storm phenomena over Chennai and its neighbourhood  is extremely rare throughout the year. However two hail storm were reported during the year 2002, one by print / electronic media on 29 May within the city limits and  the other on 30  May 2002 by a meteorological observatory maintained by Indian Navy at Arakonam located at the outskirts of city. These two storms were analysed based on the data received from the newly installed Doppler Weather Radar at Cyclone Detection Radar station, Chennai. The analysis reveals that the vertical extent of the hailstorms was well beyond 20 km and reflectivity as high as 45 dBZ was seen even at 18.5 km. The reflectivity at 3 km height was exceeding 58 dBZ which is well above the operational threshold limit for hail warning, viz.,  50 dBZ at 3 km adopted by NEXRAD, USA (Atlas, 1990).  More than 55 dBZ reflectivity was measured between 5 and 10 km altitude during the passage of hail storm. Moreover the 45 dBZ level at different stages of the storm was atleast 4.5 km above the freezing level permitting the growth of hail stones upto and beyond 10 km height a.g.l. The vertically integrated liquid (VIL) was more than 43 kg m-2 (at times more than 50 kg m-2) about an hour before the hails were observed at surface and it was between 58.7 and 64.7 kg m-2 just at the time of the hailstorm physically observed. Velocity divergence of 46 mps over the storm area at 18 km altitude confirms that hails of  19 mm was more probable with 0.80 probability. The enhanced hail detection algorithm (build 9) of NEXRAD has been verified for the severe hail index (SHI), probability of severe hail (POSH) and maximum expected hail size (MEHS) calculations and these confirmed the possibility of hail over these two locations and some more locations in the passage of the storm on these two dates.